2018
DOI: 10.26832/24566632.2018.0304012
|View full text |Cite
|
Sign up to set email alerts
|

Current status of bacterial wilt (Ralstonia solanacearum) disease in major tomato (Solanum lycopersicum L.) growing areas in Egypt

Abstract: A survey was carried out to determine the current status of bacterial wilt (Ralstonia solanacearum) disease in major tomato growing areas in Egypt incidence and distribution. In the 2014/2015 cropping season in major tomato growing areas of Upper and Lower Egypt. In upper highest incidence of bacterial wilt occurred in Luxour Governorate (10.29%) and lowest in Al-Giza Governorate (9.41%). Wilt severity was recorded (3.44%) in Luxour Governorate and the lowest (2.60%) was recorded in Sohag Governorate. In Lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…According to Liu et al, 2017 the incidence of tobacco bacterial wilt is about 15-75% causing 50-100% yield losses. In case of tomatoes, the disease incidence ranged from 9.41% to 15.28% in Egypt (Elnaggar et al, 2018). From the result of this study, it is revealed that the bacterial wilt severity ranged from 4.67-0.67 (on the basis of a 1-5 scale) in the sampled locations.…”
Section: Discussionmentioning
confidence: 72%
“…According to Liu et al, 2017 the incidence of tobacco bacterial wilt is about 15-75% causing 50-100% yield losses. In case of tomatoes, the disease incidence ranged from 9.41% to 15.28% in Egypt (Elnaggar et al, 2018). From the result of this study, it is revealed that the bacterial wilt severity ranged from 4.67-0.67 (on the basis of a 1-5 scale) in the sampled locations.…”
Section: Discussionmentioning
confidence: 72%
“…In the current scenario, bacterial wilt has a worldwide distribution, found in almost all continents and threatening the agricultural community of the globe ( EPPO, 2020 ; Gorfu, Woldegiorgis & Kassa, 2013 ). Likewise, bacterial wilt distributed to many African countries and became one of serious potato production constraints in Burundi, Cameroon, Egypt, Ethiopia, Kenya, Madagascar, Nigeria, Rwanda and Uganda, to mention some ( Kabeil et al, 2008 ; CTA, 2014 ; Elnaggar et al, 2018 ; Abdurahman et al, 2019 ; Tessema et al, 2020 ). Major seed potato exporting countries like Canada, Netherlands, France and United Kingdom ( van Loon Kees, 2007 ) as well as seed potato importing countries of Africa like Algeria, Egypt, Morocco and Tunisia are highly influenced by potato bacterial wilt.…”
Section: Importance Of Bacterial Wiltmentioning
confidence: 99%
“…Marriam Nawaz 1,3 , Tahira Nazir 2 , Ali Javed 3 , Momina Masood 1 , Junaid Rashid 4* , Jungeun Kim 4,5* & Amir Hussain 6 Tomato plants' disease detection and classification at the earliest stage can save the farmers from expensive crop sprays and can assist in increasing the food quantity. Although, extensive work has been presented by the researcher for the tomato plant disease classification, however, the timely localization and identification of various tomato leaf diseases is a complex job as a consequence of the huge similarity among the healthy and affected portion of plant leaves.…”
Section: A Robust Deep Learning Approach For Tomato Plant Leaf Diseas...mentioning
confidence: 99%